EFEKTIFITAS MODEL COOPERATIVE LEARNING TEKNIK JIGSAW DALAM PEMBELAJARAN DOKKAI II (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2015)
This research is an experiment research for study model in jigsaw co-operative learning effectivity. The sample research is second grade academic years 2013/2014 students in dokkai II subject. Based on the result, gaining the average of study result in post test with the average value is 7,65 point at experiment class and 8,26 point at control class. therefore is 0,86 point. Moreover, is smaller than , so Hk is unaccepted. Thus, in dokkai II subject was uneffective on co-operative learning in jigsaw method. Because the students attend three classes before dokkai II class from 14.20, students feel saturated, worn out and unconcentration. wherefor those few factor comprehensive analysis is too less on expert group student, random group student can’t explained crearly on their own group. Furthermore, the control class teacher always use discourse lecture, the students are accustomed to a class like that. Then study method in that control class is reading together and interpreting each sentences of the reading contents. wherefore, student’s mind set is equal and unattracted of some debate, and then students understand more about the reading contents, discussing together directly.